Social Comparison and Effort Provision: Evidence from a Field Experiment. Issue 4 (1st August 2014) - Cohn, Alain; Fehr, Ernst; Herrmann, Benedikt; Schneider, Frédéric
Abstract: Social comparison has potentially far reaching consequences in many economic domains. We conducted a field experiment to examine how social comparison affects workers' effort provision if their own wage or that of a co-worker is cut. Workers were assigned to groups of two, performed identical individual tasks, and received the same performance-independent hourly wage. Cutting both group members' wages caused a decrease in performance. But when only one group member's wage was cut, the affected workers decreased their performance more than twice as much as when both workers' wages were cut. This finding indicates that social comparison among workers affects effort provision because the only difference between the two wage-cut treatments is the other group member's wage level. In contrast, workers whose wage was not cut but who witnessed their group member's pay being cut displayed no change in performance relative to the baseline treatment in which both workers' wages remained unchanged. This indicates that social comparison exerts asymmetric effects on effort.